Recovery of Lactobacillus casei strain Shirota (LcS) from faeces of healthy Singapore adults after intake of fermented milk - Khine WWT; Ang XJ; Chan YS; Lee WQ; Quek SY; Tan SH; Teo HTA; Teo JKB; Lau QC; Lee YK (WAGENINGEN ACADEMIC PUBLISHERS, 2025)
To validate survival of Lactobacillus casei strain Shirota (LcS) during passage through the gastrointestinal tract of healthy Singaporean young adults, 21 participants (18-25 years old) were asked to consume a 100 ml of fermented milk drink containing 1.0x10(8) cfu/ml of LcS daily for 14 days, and to maintain their dietary habit and life style. During and at the end of the ingestion period, both culture method (identity confirmed by ELISA) and 16s rRNA sequencing results revealed that viable LcS (7.27 and 7.64 log(10) cfu/g of faeces at the ingestion period Day 7 and Day 14, respectively) and Lactobacillus could be recovered from the faeces of all the subjects. The viable LcS count from male and female were comparable for each time point. Before consumption (baseline) and 14 days after cessation of consumption of the fermented milk, LcS was not detected in most of the subjects. In this study condition, the composition of the major gut microbiota (>0.1% in relative abundance of genus) and characteristics of defaecation such as stool consistency and frequency of defecation did not change throughout the study before and after ingestion of LcS. LcS was able to survive passage through the gastrointestinal tract of Singapore adults without sustainable colonisation, but the effect of LcS on microbiota modulation, stool consistency and frequency was not observed under this study condition.